(untitled) (TAMADDUN NURI JURNALI, 2024)
In this article, the incomes and expenses of the residents of Kashkadarya region, problems in the regions are analyzed based on a survey of 400 people. People of various professions from all districts of the region took part in the survey. Household income includes cash income and benefits in kind, and consists of income received by the household or individual members of the household or its individual members on a regular basis, with a recurring nature, for a period of time of one year or less. It is important to note the relationship between the concepts of "income" and "wealth". In our opinion, the concept of "wealth" is broader. Income consists of the current stock of money, wealth and services of the members of society and is not always related to their use through consumption.